An international measure of awareness and beliefs about cancer: development and testing of the ABC. Issue 6 (18th December 2012) - Simon, Alice E; Forbes, Lindsay J L; Boniface, David; Warburton, Fiona; Brain, Kate E; Dessaix, Anita; Donnelly, Michael; Haynes, Kerry; Hvidberg, Line; Lagerlund, Magdalena; Petermann, Lisa; Tishelman, Carol; et al.
Abstract : Objectives: To develop an internationally validated measure of cancer awareness and beliefs; the awareness and beliefs about cancer (ABC) measure. Design and setting: Items modified from existing measures were assessed by a working group in six countries (Australia, Canada, Denmark, Norway, Sweden and the UK). Validation studies were completed in the UK, and cross-sectional surveys of the general population were carried out in the six participating countries. Participants: Testing in UK English included cognitive interviewing for face validity (N=10), calculation of content validity indexes (six assessors), and assessment of test–retest reliability (N=97). Conceptual and cultural equivalence of modified (Canadian and Australian) and translated (Danish, Norwegian, Swedish and Canadian French) ABC versions were tested quantitatively for equivalence of meaning (≥4 assessors per country) and in bilingual cognitive interviews (three interviews per translation). Response patterns were assessed in surveys of adults aged 50+ years (N≥2000) in each country. Main outcomes: Psychometric properties were evaluated through tests of validity and reliability, conceptual and cultural equivalence and systematic item analysis. Test–retest reliability used weighted-κ and intraclass correlations. Construction and validation of aggregate scores was by factor analysis for (1) beliefs about cancer outcomes, (2) beliefs about barriers to symptomatic presentation, and item summation for (3) awareness of cancer symptoms and (4) awareness of cancer risk factors. Results: The English ABC had acceptable test–retest reliability and content validity. International assessments of equivalence identified a small number of items where wording needed adjustment. Survey response patterns showed that items performed well in terms of difficulty and discrimination across countries except for awareness of cancer outcomes in Australia. Aggregate scores had consistent factor structures across countries. Conclusions: The ABC is a reliable and valid international measure of cancer awareness and beliefs. The methods used to validate and harmonise the ABC may serve as a methodological guide in international survey research.